2021
DOI: 10.3390/agronomy11122564
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fig Tree (Ficus carica L.) Leaf Aqueous Extract on Seed Germination and Seedling Growth of Three Medicinal Plants

Abstract: Fig tree cultivation land resources are not fully utilized and introducing them into sustainable medicinal agroforestry systems can effectively achieve resource protection and reuse. Laboratory and pot experiments were applied to study the allelopathic effects of fig tree (Ficus carica L.) leaf aqueous extract at five mass concentrations of 8.3, 10.0, 12.5, 16.7, and 25.0 g/L on the morphological and physiological indexes of mint (Mentha haplocalyx Briq.), dandelion (Taraxacum mongolicum Hand.-Mazz.), and woad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The intrinsic factors affecting the photosynthetic efficiency of plants can be divided into two broad categories: stomatal and non-stomatal limitations. The former mainly involve the partial closure of stomata in leaves, whereas the latter mainly exert adverse effects on the quantum efficiency of photosystem II, leading to the degradation of chlorophyll molecules and a reduction in the photosynthetic rate ( Li et al., 2021a ). In the present study, P n and C i exhibited a trend of initially increasing followed by a decrease with increasing extract concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic factors affecting the photosynthetic efficiency of plants can be divided into two broad categories: stomatal and non-stomatal limitations. The former mainly involve the partial closure of stomata in leaves, whereas the latter mainly exert adverse effects on the quantum efficiency of photosystem II, leading to the degradation of chlorophyll molecules and a reduction in the photosynthetic rate ( Li et al., 2021a ). In the present study, P n and C i exhibited a trend of initially increasing followed by a decrease with increasing extract concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Mira et al [46] reported the allelopathic effect of Pteridium aquilinum on the germination and growth of economically important weeds. In addition, Li et al [16] studied the effects of aqueous fig leaf (Ficus carica L.) extracts on seed germination and seedling growth in three medicinal species and found that these negatively affected germination, but promoted development.…”
Section: Discussionmentioning
confidence: 99%
“…Various weeds and wild plants that grow and develop in cultivated fields can contain allelopathic substances that affect seed germination [30]. Various studies, i.e., [15,16,31], have indicated that most allelopathic substances, such as secondary metabolites, are synthesized through the metabolic shikimic acid and isoprene pathways. The known allelopathic substances mainly include phenols, quinones, karinas, flavonoids, terpenes, sugars, glycosides, alkaloids, and non-protein amino acids [32].…”
Section: Effect Of V Sphaerocephala and V Fastigiata Extracts On The ...mentioning
confidence: 99%
See 2 more Smart Citations